Major Bleeding During Thrombolytic Therapy for Acute Lower Limb Ischaemia: Value of Laboratory Tests for Clinical Decision Making, 17 Years of Experience. (March 2023) - Doelare, Sabrina A.N.; Oukrich, Safae; Ergin, Kübra; Jongkind, Vincent; Wiersema, Arno M.; Lely, Rutger J.; Ebben, Harm P.; Yeung, Kak K.; Hoksbergen, Arjan W.J.; ,
Abstract : Objective: Regular measurement of fibrinogen as dose guidance in catheter directed thrombolysis (CDT) for acute limb ischaemia (ALI) has recently been dropped from European guidelines based on inconsistent literature. This study aimed to determine whether low fibrinogen levels and high activated partial thromboplastin time (APTT) are associated with an increased major bleeding risk during CDT. Methods: All consecutive patients treated with CDT for ALI in two Dutch hospitals between January 2004 and April 2021 were analysed retrospectively. Patients were treated with two dosing regimens (low dose: 50 000 IU/hour; high dose: 100 000 IU/hour) of urokinase and, after 2018, with a single low dose regimen of alteplase (rtPA) due to urokinase manufacturing problems. The incidence of major bleeding and associated APTT and fibrinogen levels were reviewed from patient charts. Results: Of the 443 included cases, 277 underwent CDT with urokinase and 166 with rtPA. The incidence of major bleeding in the whole cohort was 7%. Patients with a fibrinogen levels < 1.0 g/L developed more major bleeding than those in whom the fibrinogen level did not drop below 1.0 g/L (15% vs. 6%; p  = .041). Systemic heparinisation during CDT or high (> 80 seconds) APTT were not significantly associated with major bleeding. Angiographic success (47% vs. 72%; p  = .003) and 30 day amputation free survival (53% vs. 82%; p < .001) were lower for cases with major bleeding. Older age (odds ratio [OR] 1.06, 95% confidence interval [CI] 1.02 – 1.11), cardiac history (OR 3.35, 95% CI 1.39 – 8.06), high dose regimens (≥ 75 000 IU/hour urokinase; OR 2.67, 95% CI 1.18 – 6.04), and fibrinogen values < 1.0 g/L (OR 5.59, 95% CI 1.98 – 15.77) were independent predictors for major bleeding during CDT. Conclusion: High dose thrombolytic regimens and fibrinogen levels of ≤ 1.0 g/L are associated with more major bleeding during thrombolytic therapy. Major bleeding significantly worsened the clinical outcome. A prospective comparative study is needed to assess the benefit of monitoring fibrinogen levels.